The Monte-Carlo refractive index matching technique for determining the input parameters for simulation of the light collection in scintillating crystals - Wahl, D; Mikhailik, V; Kraus, H (2007)
The Monte-Carlo refractive index matching (MCRIM) technique was developed to determine the physical properties of heavy inorganic scintillators (HIS) which are difficult to measure experimentally. It was designed as a method for obtaining input parameters for Monte-Carlo (MC) simulations of experimental arrangements incorporating HIS in their setups. The MCRIM technique is used to estimate the intrinsic light yield, the scattering coefficient and the absorption coefficient, herein referred to as indirect measurement properties. The MCRIM technique uses an experiment/MC combination to determine these indirect measurement properties. The MCRIM experimental setup comprises a crystal placed on a photomultiplier tube window with the possibility of introducing materials of different refractive indices in a small gap between the crystal and photomultiplier tube (PMT) window. The dependence of the measured light yield on the refractive index of the material in the gap can only be reproduced by simulations if the correct values of scattering, absorption and intrinsic light yield are used. The experimental setup is designed to minimise the presence of optical components such as unpolished surfaces and non-ideal reflectors, which are difficult to simulate. The MCRIM technique is tested on a 1.03×1.00×0.82 cm3 crystal of CaWO4 which is found to have a scattering coefficient of 0.061±0.005 cm-1, an absorption coefficient of 0.065±0.005 cm-1, and an intrinsic light yield of 22700±1700 photons/MeV. © 2006 Elsevier B.V. All rights reserved.